The seventh ENBDC workshop on methods in mammary gland development and cancer. Issue 1 (December 2015) - Glukhova, Marina; Hynes, Nancy; Vivanco, Maria; van Amerongen, Renée; Clarke, Robert; Bentires-Alj, Mohamed
Abstract The seventh annual meeting of the European Network of Breast Development and Cancer Laboratories, held in Weggis, Switzerland, in April 2015, was focused on techniques for the study of normal and cancer stem cells, cell fate decisions, cancer initiation and progression.